KENDALA PERKEMBANGAN POTENSI MASYARAKAT - Studi Kasus di Kelurahan Kawatuna, Kota Palu - (Constraints to The Developmental of Societal Potential: Case Study in Kawatuna, Palu City) - Achmadi Jayaputra (Politeknik Kesejahteraan Sosial, 2005)
The impact of uncoordinated handling of social-economic problems in community is the occurrence of constrains for the development of societal potential. In enerally, is assumed thatthe causes of poverty can be come from internal factors such as the limited education and skillbased on local potentials, Whereas the external factors causing povertyare less pro-poor of thegovernment policy disaster, This research is aimed at identifying poverty programs and it'sconstraints focusing on the development of societal potential. The respondents of this research are local readers and managers of local institutions at Kelurahan Kawatuna district of Palu Selatan, The City of Palu. Result of this research found that constraints for the development of societal potential are economic problems and the lack of human resources. These factors seem to have reduced the effectiveness of empowering natural and social resources.